2015
DOI: 10.1371/journal.pone.0137128
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Active Pro-Fibrotic Response in Blood of Patients with Cirrhosis

Abstract: The role of systemic immunity in the pathogenesis of cirrhosis is not fully understood. Analysis of transcriptomic profiles in blood is an easy approach to obtain a wide picture of immune response at the systemic level. We studied gene expression profiles in blood from thirty cirrhotic patients and compared them against those of eight healthy volunteers. Most of our patients were male [n = 21, 70%] in their middle ages [57.4 ± 6.8 yr]. Alcohol abuse was the most frequent cause of cirrhosis (n = 22, 73%). Eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In several independent transcriptomic analyses of NASH, cirrhosis and HCC in human, TGFB1 was consistently up-regulated [ 14 , 23 , 24 ]. However, a lack of coherent study across different stages of the liver disease on TGFb1 expression and its downstream activation hindered the understanding of the chronical effect of TGFB1.…”
Section: Resultsmentioning
confidence: 99%
“…In several independent transcriptomic analyses of NASH, cirrhosis and HCC in human, TGFB1 was consistently up-regulated [ 14 , 23 , 24 ]. However, a lack of coherent study across different stages of the liver disease on TGFb1 expression and its downstream activation hindered the understanding of the chronical effect of TGFB1.…”
Section: Resultsmentioning
confidence: 99%
“…Men et al 25 demonstrated that TNXB mapped in pathways of focal adhesion, ECM receptor interaction, and calcium signaling pathway. Sanchez‐Antolín et al 37 previously reported that TNXB affected the activation of the TGF‐β signaling, and TGF‐β could interact with the PI3K‐Akt signaling, potentially 38 . Since the exact role or mechanism of TNXB in ESCC remained largely undiscovered, here, we conducted co‐expression and gene set enrichment analysis using mRNA expression data in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the histological findings, we searched for the expression of specific genes that contribute to fibrosis and inflammation (Figure 4 and supplementary table). Col27A1 and Col5A1, two genes belonging to the collagen class and were shown to be increased in cirrhosis, 32 were upregulated in the liver of vehicle-treated HFD-fed mice but not in the b-LGND2-treated HFD-fed mice. On the other hand, expression of inflammatory genes such as CxCl1, which are involved in neutrophil chemoattractant properties, 33 were up-regulated in the liver of vehicle-treated HFDfed mice but not in the b-LGND2-treated HFD-fed mice.…”
Section: Rna Sequencing Studies Indicate That B-lgnd2 Inhibited Pregnmentioning
confidence: 94%